Modelling a semi-batch reative precipitation of ferrihydrite - Richmond, William; Li, T.; Ilievski, D. (Met Soc, 2005)
The reactive precipitation of ferrihydrite was studied in a laboratory semi-batch precipitator, where a highly concentrated sodium hydroxide solution was fed into an iron nitrate solution. Instantaneous hydrolysis of iron[III] takes place when the two reagents are mixed generating supersaturation, and leading to immediate precipitation of ferrihydrite via a primary nucleation mechanism then followed by limited crystallite frowth to 3 to 7nm. A mathematical model of the semi-batch laboratory precipitator was used to simulate the pH responses during the precipitation of ferrihydrite at different reagent feed rates. The model comprised of interconnected compartments of averaged hydrodynamic conditions, incorporating physically meaningful turbulent mixing time constants. The precipitation process is described by the solute concentration conservation equation incorporating a postulated ferrihydrate primary nucleation model. It was found that the semi-batch precipitator model predicted teh experimental pH response reasonable well. The experimental results demostrated that the reagent feed rate has a critical effect on the course of the precipitation of ferrihydrite, i.e. it is a rate determining step given the fast hydrolysis and precipitation kinetics.